Виховання у дітей старшого дошкільного віку впевненості у собі - Скок, Марина Олегівна (My University, 2025)
Matviienko A.A. Development of speech activity in older preschool children through mnemonics. Manuscript. Nizhyn, 2025. – 85 p. The qualification paper has been carried out at both theoretical and practical levels. At the theoretical level, the content and structure of key categories have been clarified, and theoretical aspects of developing speech activity in older preschool children by means of mnemonics have been analyzed. At the empirical level, the components, criteria, indicators, and levels of speech activity formation in older preschoolers have been determined; the level of speech activity formation in older preschool children has been studied, as well as the influence of educators on the development of this quality in children. Pedagogical conditions have been identified, and a system of work for developing speech activity in older preschool children through mnemonics has been developed. Keywords: “speech,” “speech development,” “speech activity,” “activity,” “active speech,” “speech activity,” “communicative speech activity,” “mnemonics.”
The topic of the qualification work “Education of self confidence in children of senior preschool age” was studied at the theoretical and empirical levels. The results are presented in two sections of the work. At the theoretical level, the state of development of the problem by domestic and foreign specialists is characterized; the content and structure of the leading category are determined; the features of the development of self confidence in preschool childhood are revealed; pedagogical conditions for optimizing the process of educating the studied quality in preschool education are substantiated. In order to solve the empirical tasks of the study, a program and methodology for a ascertaining experiment have been developed; criteria, indicators and structural components of self--confidence in children aged 5--7 years have been determined; the levels of formation of this quality in the studied senior preschoolers are described; a system for forming self--confidence has been developed, pedagogical conditions for optimizing the educational process are substantiated, and methods for educating this strong--willed quality in children aged 5--7 years have been revealed. Key words: confidence as a personality phenomenon, confidence--insecurity--self--confidence, adequate self--esteem, optimization of the educational process, developmental environment, educational innovations.
Keywords: впевненість; впевненість у собі; невпевненість; самовпевненість; самооцінка; розвивальне середовище; освітні інновації